2022
DOI: 10.1021/acssuschemeng.2c03372
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Urea Nanosack: Jute Grafted Silica Nanoring Woven Fertilizer to Control Urea Release and Enhance Crop Productivity

Abstract: A sustainable fertilizer coating using silica for urea release control has been developed using egg white as the binder, which forms an irreversible hydrophobic β-sheet on gentle heating and substitutes earlier petrochemical coatings. When the silica content is increased for diffusion control, the membrane becomes brittle; hence, for the first time here, jute grafted silica nanoring has been used, where the nanojute acts as a strong buckle for the egg white β-sheet fastener and serve as the sack for holding ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(73 reference statements)
0
12
0
Order By: Relevance
“…The FITR spectra of CRU1 and SCRU1 showed that the characteristic peaks of N-H shift to the left at 3420 cm −1 and 3432 cm −1 , the characteristic peaks of βN-H shift to the right at 1620 and 1536 cm −1 , and showed the characteristic absorption peaks representing C-O-C bonds [43] at 1227 cm −1 and 1230 cm −1 (CRU1 and SCRU1 in Fig. 8), but the tensile vibration of SCRU1 modified by DS was more obvious than that of CRU1.…”
Section: Structural Analyses Of Eb Leb1 Ds Cru1 and Scru1 By Ftir Spe...mentioning
confidence: 99%
“…The FITR spectra of CRU1 and SCRU1 showed that the characteristic peaks of N-H shift to the left at 3420 cm −1 and 3432 cm −1 , the characteristic peaks of βN-H shift to the right at 1620 and 1536 cm −1 , and showed the characteristic absorption peaks representing C-O-C bonds [43] at 1227 cm −1 and 1230 cm −1 (CRU1 and SCRU1 in Fig. 8), but the tensile vibration of SCRU1 modified by DS was more obvious than that of CRU1.…”
Section: Structural Analyses Of Eb Leb1 Ds Cru1 and Scru1 By Ftir Spe...mentioning
confidence: 99%
“…14,15,39 The details of mathematical models are given in Table 1. The experimental potassium quantification data were fitted to the following kinetics equation: 14…”
Section: Release Behaviour and Mechanismmentioning
confidence: 99%
“…The dried harvested grains were weighed separately and referred to as grain/economic yield. The increase in economic and biological yield percentage for each treatment over control was calculated using the following equation: 14 Increase yield %…”
Section: Plant Growth Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These environmental issues seriously affect the sustainable development of agricultural production [9]. Therefore, finding efficient and environmentally friendly fertilizers has become the key [10,11], and new controlled-release fertilizers are one of the important types [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%